ANALISIS PENGARUH KUALITAS FITUR APLIKASI DRIVER SHOOPEFOOD TERHADAP TINGKAT KEPUASAN MITRA DI MAKASSAR - Karmila Karmila (Universitas Ichsan Sidenreng Rappang, 2025)
The ShopeeFood Driver app is designed to provide opportunities and employment in the online food delivery sector, but it still has several shortcomings related to its features. This study aims to analyze the effect of the quality of the ShopeeFood Driver app's features on the satisfaction level of driver partners in Makassar. In the digital economy, the quality of app features is a crucial factor influencing the effectiveness and satisfaction of ShopeeFood driver partners. This research approach is quantitative and descriptive, with the researcher directly involved in the data collection, observation, and interpretation process in the field. Data were obtained through questionnaires with 20 ShopeeFood driver partners in the Makassar area. The results showed an average feature quality of 3.56 and partner satisfaction of 3.63, which are considered good indicators. This result indicates that the better the feature quality, the higher the partner satisfaction level. This finding confirms that improving the quality of app features has a direct impact on partner satisfaction and loyalty.